Preparation and biological performance of poly(vinyl alcohol)/hydroxyapatite porous composites used for cartilage repair. Issue 102 (20th October 2016) - Qiu, Wenting; Wang, Jia; Li, Li
Abstract : PVA/HA porous materials with proper cell structure and biological properties which were suitable for cartilage repair were prepared via thermoplastic foaming technique by using water/ethanol as co-blowing agent. Abstract : Poly(vinyl alcohol) (PVA)/hydroxyapatite (HA) porous composites were prepared via thermoplastic molding foaming technology by using water/ethanol as co-blowing agent, and the effects of HA content on cell structure and various properties including tribological properties, fatigue properties as well as biocompatibility of the porous composites were investigated to evaluate their suitability as the potential material for cartilage repair. The results showed that with the increase of HA content, porous composite with a denser cell structure was achieved. The addition of HA improved the friction properties of the porous composites, making both sliding friction coefficient and rotational friction coefficient decreased. The lowest value of rotational friction coefficient was 0.025, so close to that of human bone. Most importantly, the porous composites presented excellent fatigue properties and possessed good cytocompatibility, so were suitable for bone tissue restoration in theory.